Contribuições de uma política pública de avaliação institucional para a Universidade Federal do Amapá - Guimarães, Maria Nazaré do Nascimento (2012)
This study is part of the evaluation of higher education field, specifically in one of the evaluative processes implemented by the Ministry of Education in Brazil, the National Higher Education Evaluation System (SINAES in Portuguese). It refers to a survey conducted in a public institution of higher education in the municipality of Macapá-AP and aimed to investigate how it is been the implementation process of a public policy of institutional assessment at the Federal University of Amapá in Teaching degree courses under the perspective of teachers and members of the Assessment Committee. It is constituted as the theoretical framework of this study authors such as, Dias Sobrinho (2000-2010) Polidori and Barreyro (2006-2009), Sordi (2002-2011), among others of relevance in the field of higher education assessment. The study of qualitative nature is constituted of a case study, because it is a research involving a single institution and a specific evaluation program, and had as a source of data collection to document analysis, the semi - structured interviews with CPA members, and with teachers, conducting focal groups. The research has shown that teachers of the four Teaching degree courses and CPA members understand that the institution it is been experiencing a gradual process of change in relation to the conceptions and directions of public policy, recognizes its importance, the same way they want to participate in the evaluation process and that the results could serve as a basis for the development of institutional policies for the IES investigated.